Complementary Relationship Among Heat Flux Ratios and Maximum Entropy Production Principle in Humid Forests - Kwanghun Choi; Kyungrock Paik (Water Resources Research)
Abstract Understanding how the net Solar radiation is partitioned into heat fluxes on land surface is fundamental to understand water, energy, and carbon cycles. Here we claim that, in forests under energy‐limited environment, the proportion in the net radiation occupied by the sum of the sensible and latent heat fluxes rarely varies over time; the variability in the latent heat fraction is mostly compensated by that of the sensible heat flux. This mutual compensation is rooted in the energy conservation principle and also in accordance with the principle of Maximum Entropy Production (MEP). The ratio of inertia parameters corresponding to latent and sensible heat fluxes in the MEP‐based model, is found approximately the reciprocal Bowen ratio. With this seesaw relationship, the formulation of the MEP‐based model for the surface energy partitioning problem is simplified. The new formulation is tested for a wide range of flux tower sites with different biome, demonstrating promising results.